2020
DOI: 10.3389/fnmol.2019.00330
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes and Microglia Are Resistant to NAD+-Mediated Cell Death Along the ARTC2/P2X7 Axis

Abstract: ADP-ribosylation of the P2X7k splice variant on mouse T cells by Ecto-ADPribosyltransferase ARTC2.2 in response to its substrate extracellular nicotinamide adenine dinucleotide (NAD + ) triggers cell death. Since NAD + is released as a danger signal during tissue damage, this NAD + -induced cell death (NICD) may impact the survival of other cell populations co-expressing P2X7 and of one of the ARTC2 isoforms (ARTC2.1, ARTC2.2). NICD of brain-resident, non-T cell populations has only been rudimentarily investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
0
9
1
Order By: Relevance
“…Isolation of primary cells. Isolation of primary cells was described before 50 . For the isolation of brain microglia, mice were sacrificed under anesthesia by cervical dislocation.…”
Section: Sds-page and Western Blot Analysismentioning
confidence: 99%
“…Isolation of primary cells. Isolation of primary cells was described before 50 . For the isolation of brain microglia, mice were sacrificed under anesthesia by cervical dislocation.…”
Section: Sds-page and Western Blot Analysismentioning
confidence: 99%
“…GLAST1 is a known cell surface marker expressed on microglia and astrocytes 50 . To differentiate between the microglia and astrocytes in all of the samples, flow cytometry analyses were done, and microglia were identified as CD11b + GLAST1 − cells and astrocytes as CD11b − GLAST1 + , as previously explained 51 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Rissiek et al (2020) reported that the dominant P2X7 receptor in mouse astrocytes in culture is P2X7a, a splice variant that is much less sensitive to NAD + /ARTC2‐mediated ADP‐ribosylation (Rissiek et al, 2020). In the present study, however, we showed that P2X7 receptor‐mediated responses were dramatically increased by NAD + in astrocytes.…”
Section: Discussionmentioning
confidence: 99%